Evaluation of the Effectiveness of Mathematics and Natural Sciences Learning at SMA Negeri 5 Karawang through a Scientific Approach - Hikmah Masudah; Hendro Prasetyono (MASALIQ, 2026)
This study evaluates the effectiveness of implementing a scientific approach in mathematics and natural science learning at SMA Negeri 5 Karawang, focusing on its influence on student learning outcomes, learning activities, and teacher competence. Using a mixed-method design with a pretest–posttest model and descriptive observations, the research involved 90 students of class XI MIPA and 6 MIPA teachers. Data were collected through learning outcome tests, student activity observation sheets, and teacher competency evaluations, and analysed using descriptive statistics and gain scores. The findings show that the scientific approach significantly enhances student learning outcomes, with the average pretest score of 70.15 increasing to 82.01 on the posttest, representing a 16.9% improvement and an N-Gain score of 0.47 in the moderate category; the greatest progress was observed in reasoning skills (C4) and the application of concepts (C3), indicating strengthened critical and analytical thinking. Student learning activities also improved at each stage of the scientific process: observation increased from 70% to 88%, questioning from 61% to 84%, experimenting from 65% to 86%, reasoning from 63% to 85%, and communicating from 67% to 86%, resulting in an overall increase of 20.6% in the high category and reflecting more active, creative, and collaborative engagement. From the teacher’s perspective, competence in implementing the scientific approach reached an average score of 3.3 in the good category, with the highest score in lesson planning (3.7) and the lowest in guiding scientific communication (2.9), suggesting the need for further professional development in facilitating student reporting and presentation of experimental findings. Overall, the study concludes that the scientific approach is effective in improving student learning outcomes and classroom activities while supporting teacher competence, and it provides empirical evidence to inform efforts to strengthen teaching practices and targeted capacity-building in scientific communication.